Evaluación de la planta de tratamiento de agua potable de la parroquia San Juan de Cerro Azul del cantón Atahualpa. - Andrade Ochoa, Elvis Mauricio (Machala : Universidad Técnica de Machala, 2018)
The project is based on the technical evaluation carried out at the drinking water treatment plant in the San Juan parish of Cerro Azul of the Atahualpa district, in the province of El Oro. The present is intended to provide a technical solution considering the geographical context, with the aim of improving water quality for the current population and with projections to the future population, in such a way that it improves the quality of life and helps to reduce the risk of contracting diseases caused by poorly treated water. It is important to mention that, when implementing the technical solution, the current infrastructure of the treatment plant will be conserved, prioritizing the rehabilitation of its elements, activating the operative phase of the same. After the evaluation of its elements, it was identified that the pre-filter lacks the granular material, one of the slow filters is not operational, aspects such as the ones described above prevent the correct operation of the treatment plant, resulting in the plant perform only 50% of the total operation for which it was designed. The physical-chemical and bacteriological analyzes show the presence of fecal coliforms in quantities greater than the maximum permissible limits, a problem caused by the lack of chlorine dosage.
El proyecto parte de la evaluación técnica realizada a la planta de tratamiento de agua potable, en la parroquia San Juan de Cerro Azul del cantón Atahualpa, en la provincia de El Oro. Con el presente se pretende dar una solución técnica considerando el contexto geográfico, con el objetivo de mejorar la calidad de agua para la población actual y con proyecciones a la población futura, de tal manera que se logre mejorar la calidad de vida y contribuyendo a disminuir el riesgo de contraer enfermedades causadas por el agua mal tratada. Es importante mencionar que, al implementar la solución técnica, se conservará la infraestructura actual de la planta de tratamiento priorizando la rehabilitación de sus elementos, activando la fase operativa de la misma. Posterior a la evaluación de sus elementos, se identificó que el pre-filtro carece del material granular, uno de los filtros lentos no está operativo, aspectos como los antes descritos impiden el correcto funcionamiento de la planta de tratamiento, dando como resultado que la planta realice solo el 50 % del funcionamiento total para el que fue diseñada. Los análisis físicos-químicos y bacteriológicos demuestran la presencia de coliformes fecales en cantidades mayores a los límites máximos permisibles, problemática causada por la falta de dosificación del cloro.
Keywords: EVALUACION; PLANTA DE TRATAMIENTO; AGUA POTABLE; FILTRACION LENTA